Isolasi Dan Identifikasi Bakteri Tanah Burkholderia Pseudomalllei Penyebab Melioidosis Di Kota Makassar - Munir, Nur Faidah; Munir, Nur Wahyuni; Zainuddin, Zaraswati D (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
Burkholderia pseudomallei is a type of saprophytic bacteria, is an opportunistic pathogen, and as a causative agent of melioidosis. These bacteria are found living in soil, water, and agricultural fields. Cases of melioidosis have been widely reported in Asian countries, but there is not much specific information regarding the incidence of these diseases in Indonesia. The study aims to identify the soil bacteria Burkholderia pseudomalllei in Makassar City. Sampling was carried out randomly in 11 districts in Makassar City, namely Mamajang, Tamalate, Rappocini, Mariso, Bontoala, Wajo, Biringkanaya, Manggala, Tamalanrea, Tallo, and Makassar. Data analysis uses descriptive qualitative methods in the form of figures and tables. Cultivation of isolates using selective medium Ashdown Agar. Identification of bacteria using gram staining, and several biochemical tests. The results were obtained as many as 100 isolates of samples, each of 28 isolates of Burkholderia pseudomalllei positive samples and 72 isolates of other types of bacteria. The study concluded that there was a spread of the Burkholderia pseudomallei bacterium in Makassar City, so it was suggested to be a reference for further research on melioidosis